Evaluation of local community knowledge, awareness and willingness to participate in conservation of River Terrapin in Perak River, Malaysia - Abdul Rahman, Muhammad Farhan (2017)
Malaysia is the largest last stronghold of wild river terrapin in the world habituating river throughout Peninsular Malaysia. However, recent trends show the declining of nesting female in Bota Kanan, Perak which on 2005, it is recorded only 25 female landed laying eggs during the season ended in February. Typical conservation approach program should be upgraded with the involvement of local community in order to increase the population. In attempt to understand the community, the local community will be assessed in term of their knowledge, awareness, and willing ness to participate in the conservation of river terrapin in Perak River, Malaysia. A questionnaire was design and conducted at the Perak Tengah district in Mukim Bota specifically at Kampung Bota Kanan. Considering the population size of 26,552 people, the minimum recommended sample size for this study would be 394 person at 95% confidence level. The sampling was conducted from June to December 2016 after it was pretested in Mei 2016. Collected survey responses were coded in Statistical Package for the Social Science (SPSS) and simple descriptive statistic was run. In addition, Principal Component Analysis (PCA) was also conducted. As a results, community at Bota Kanan, Perak have a good knowledge and awareness regarding the decline population of river terrapin but poor in the deeper knowledge as they did not know the nesting season and distribution of this species in Malaysia. Majority of them agree that the conservation center lack in organizing the awareness event for public and need to be upgraded and they show lack of interest to visit the conservation centre. People at Bota Kanan show a positive feedback regarding the willingness to participate in the conservation program as they will keep the Perak River clean, feel responsible to conserve terrapin and reported any illegal activities related to river terrapin. For the information transfer among community part Facebook is the most assess social media, Sinar Harian is the most preferable newspaper, TV3 is the channel with the highest rating, and Perak fm. is the main channel to listen. For the correlation part, it is show that younger person is more interested to join the conservation programme compared to the older person, education levels did not have correlation with the level of knowledge, education level have a significant correlation to willingness to participate and long-time resident know that river terrapin habituating Perak River instead of younger person which did not really know about the species. The good knowledge and awareness of the local communities will result the positive feedback on willingness to participate in the conservation programme as 95% of the respondents willing to maintain the cleanness of the river while 87% of them feel responsibility to conserve the species and 84% willing to make a report regarding any illegal activities on river terrapin. As the conclusion, managing river terrapin conservation for a long period of time is crucial to have more knowledgeable community thus build strong awareness to sustain the programme.